DEVELOPMENT OF HEMATITE ORE PELLET UTILIZING MILL SCALE AND IRON ORE SLIME COMBINATION AS ADDITIVE (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Iron ore slime is generated from the mines during processing and washing of iron ore and it is not considered for pelletizing due to its excessive fineness and high gangue content despite its good green bonding property. Mill scale is generated from the steel rolling mills and reheating furnaces, which has almost nil gangue content but is not individually considered for pelletizing due to its poor green bonding property. If the both of these two wastes are blended in combined form with hematite ore, the high gangue of slime would be balanced by the gangue free mill scale. While, mill scale will be providing exothermic heat of oxidation of FeO and Fe3O4 in it and enhance the diffusion bonding, slime will be providing good green bonding property to the pellet. Therefore, in this study a good quality pellet has been developed by the combined mixing of these two wastes in hematite ore without much increase in gangue content.  Up to 15% mill scale and 15% slime could be used successfully. The developed pellets provides improved cold compressive strength (366 kg/ pellet), reducibility index (82%) and reduction degradation index (8.5%). Induration temperature could be reduced by 75 °C, which indicates a considerable energy saving in induration furnace.